Alinhamento entre as práticas de liderança e a cultura organizacional - Souza, Leandro Gil da Silva (2006)
The work searches through the model of practical of leadership of Kouzes and Posner and Model Neo-Difusionista developed by Alvarez and Quintella, to verify the alignment between practical of leadership and organizational culture, from a survey in a German multinational assembly plant. Through the related bibliography it is displayed the theoretical recital around the concept of leadership and the concept of organizational culture demonstrating the importance of the study and application of the field tests. As a conclusion, the main perceptions of the interviewed are presented relating aspects between the applied methods